임상간호사의 자기효능감 및 지각한 사회적 지지와 심리적 소진의 관계 - 강소영(So Young Kang); 박영숙(Young Sook Park) (Seuteureseu yeon-gu (Online), 2006)
The purpose of this study was to investigate the effect of perceived social support and self-efficacy on nurses' burnout. Participants were 176 nurses working in university hospitals in Korea. Burnout was measured by the questionnaire developed by Pines (1981). Social support scale (Park, 1985), and self-efficacy scale (Kim, 1997) were used to measure each variables, perceived social support and self-efficacy. The results were summarized as follows; There were significant differences depending on age, scholarly attainments, marriage status, the length of service, and work-post. Also, there was a significant difference in the perceived social support depending on work-post, age, scholarly attainments, the marriage status, and the length of service in self-efficacy. The older they were, the longer their work-career was, and the lower degree of burnout they sensed. In the area of social support, ICU (Intensive care unit) nurse highly perceived the social support. Nurses who were older highly perceived self-efficacy. Burnout was predicted through the regression analysis. Self-efficacy was a better predictor of burnout than social support. Overall, the perceived social support and self-efficacy explained 22.6% of variance of burnout. The result of this study presented one of the methods to buffer the burnout of nurses by enhancing a cognition level of social support and by improving self-efficacy. (Korean J Str Res 2006;14:219～226) KCI Citation Count: 13